Improvement in variance estimation using transformed auxiliary variable under simple random sampling - Hameed Ali; Syed Muhammad Asim; Muhammad Ijaz; Tolga Zaman; Soofia Iftikhar (Scientific Reports, 2024)
Abstract This paper offers a novel approach to formulate efficient ratio estimator of the population variance using a transformed auxiliary variable. The impact of transformation on auxiliary information has also been discussed. It is observed that incorporating a transformed auxiliary variable result in a high gain in efficiency. Theoretical properties of the newly developed estimators have been derived. The empirical and simulation studies show that the suggested estimators outperformed the existing estimators.